Tanshinone IIA Protects Ischemia/Reperfusion-Induced Cardiomyocyte Injury by Inhibiting the HAS2/FGF9 Axis - Yanzhe Wang; Weixin Sun; Le Shen; Peng Yu; Qiusheng Shen; Yaozhong Zhou; Lu Yao; Xiaohu Chen (Cardiology Research and Practice)
Purpose. This study aimed to investigate the impacts of tanshinone IIA (Tan IIA) on ischemia/reperfusion (I/R)-induced cardiomyocyte injury in coronary heart disease (CHD), and to determine whether Tan IIA regulates myocardial cell injury induced by I/R through the Hyaluronan Synthase 2/fibroblast growth factor 9 (HAS2/FGF9) axis. Methods. Weighted gene co-expression network analysis (WGCNA) of the GSE23561 microarray dataset determined gene modules linked to CHD. The key genes were further explored through differential expression and protein-protein interaction (PPI) network analyses. Human AC16 cardiomyocytes were treated with Tan IIA, HAS2 knockdown, and FGF9 overexpression and they were exposed to normoxic, hypoxic, and I/R environments. Cell viability, apoptosis, gene/protein expression, and markers of oxidative stress were evaluated in vitro. Results. The turquoise module was significantly correlated with CHD and HAS2 was identified as a hub gene. Under hypoxic conditions, Tan IIA exhibited a dose-dependent cardioprotective effect. Tan IIA ameliorated I/R-induced cellular injury, as evidenced by increased cell viability, decreased apoptosis, and regulation of key proteins (PCNA, Bax). After I/R conditions, knockdown of HAS2 increased cell viability and reduced apoptosis, whereas overexpression of FGF9 reversed these effects. Notably, HAS2 knockdown also ameliorated I/R-induced increases in inflammatory cytokines and oxidative stress, and synergistic protection was provided by combined treatment with FGF9 and Tan IIA. Conclusion. Taken together, our findings confirm that Tan IIA protects cardiomyocytes from I/R-induced injury by controlling the HAS2/FGF9 axis. These findings reveal the potential therapeutic significance of Tan IIA in alleviating CHD-related myocardial dysfunction.